Tüen Sie au gern apéröle, käffele oder kungfule? Die Produktivität des denominalen Wortbildungsmusters der -(e)le-Verben zwischen Morphologie und Syntax - Madlener, Karin; Weder, Mirjam; Dettwiler, Sophie (Linguistik Online, 2019)
How can we measure dialectal constructional productivity? Which factors determine degrees of productivity and the acceptability of creative ad hoc coinages in the domain of derivational processes? Based on data from a pilot survey (n=80), we discuss a range of factors influencing degrees of productivity/creativity for the denominal -(e)le-verb pattern (e. g., käffele, apéröle, ipödle, kungfule) in Swiss German dialects. This morphological pattern is currently highly productive, as indicated by substantial numbers of creative ad hoc coinages (oral and written evidence) as well as our participants’ acceptability judgements (for both isolated verbs and verbs in sentences) and their elicited productions (meaning paraphrases and sentence contexts for ad hoc coinages). We discuss different types of evidence for constructional productivity, based on quantitative and qualitative data. Our data indicates that schema-based frequency/familiarity effects and analogy-based pattern extension contribute to the pattern’s productivity. The fact that the verbs’ constructional contexts partly influence their acceptability indicates that the derivational pattern stretches beyond the traditional domain of morphology such that morphological, semantic, and syntactic patterns jointly determine degrees of constructional productivity.